Two copper-based MOFs constructed from a linear diisophthalate linker: supramolecular isomerism and gas adsorption properties. Issue 20 (1st May 2019) - He, Minghui; Xu, Tingting; Jiang, Zhenzhen; Yu, Xinjian; Zou, Ying; Yang, Luyao; Wang, Xiaojuan; Wang, Xia; He, Yabing
Abstract : A pair of MOF supramolecular isomers was constructed from a linear diisophthalate ligand, and one of them displayed promising potential for C2 H2 /CH4 and CO2 /CH4 separations. Abstract : Combining a linear diisophthalate ligand, 5, 5′-(2, 3-dimethylbenzene-1, 4-diyl)diisophthalic acid, with CuCl2 ·2H2 O under different solvothermal conditions afforded two distinct copper-based metal–organic frameworks (ZJNU-96 andZJNU-97 ), which were structurally characterized by various techniques. Single-crystal X-ray diffraction analyses reveal that they contain the same inorganic and organic building units but exhibit different topological structures, thus belonging to supramolecular isomers. Furthermore, gas adsorption studies show thatZJNU-96 not only exhibits better stability against desolvation thanZJNU-97 but also displays promising potential for selective adsorptive separation of C2 H2 and CO2 from CH4, with C2 H2 (CO2 ) uptake of 183.6 (88.7) cm 3 (STP) g −1 and C2 H2 (CO2 )/CH4 (v/v, 50/50) IAST adsorption selectivity of 26.6 (5.2) at 298 K and 1 atm.